The Effectiveness of Distraction (Cartoon-Patterned Clothes and Bubble-Blowing) on Pain and Anxiety in Preschool Children during Venipuncture in the Emergency Department. (30th November 2017) - Lilik Lestari, Made Pande; Wanda, Dessie; Hayati, Happy
ABSTRACT: In preschool children, venipuncture is considered a bodily threat that can cause pain and anxiety, as well as being a traumatic experience. If the pain and anxiety felt by a child during a venipuncture is not addressed properly, it can result in a traumatic experience, and traumatic events in childhood can have long-term consequences. Atraumatic treatment in the emergency department has been little explored in previous research; therefore, the present study assessed the effectiveness of using the distractions of cartoon-patterned clothes and bubble-blowing on the pain and anxiety of preschool children during venipuncture in the emergency department. This was a quasi-experiment that used a post-test only, control group design approach. The sample consisted of 57 preschool children who were due to undergo venipuncture and who were divided into 3 intervention groups. The results showed that distraction using bubble-blowing is effective in reducing pain and anxiety during venipuncture, while cartoon-patterned clothing is only effective in reducing anxiety. Distractions can refocus the attention of a child away from pain and anxiety during venipuncture. It can inhibit the transmission of pain impulses, such that these impulses are not transmitted to the brain. As a result, the sensation of pain is not experienced.